Interdisciplinarity and Latin American Studies - Andrade A., Pablo (2007)
Two central questions lead the development of this article.  What does it mean to study Latin America today?  How fruitful has interdisciplinarity been in latin american studies?  For the author the first question seeks to find the current meaning of latin american studies in the light of past experiences and the second seeks to evaluate the acquired knowledge in its historical trajectory.